Delinquent Behavior, Violence, and Gang Involvement in China - Pyrooz, David C. (Journal of quantitative criminology, 2013)
Objectives This study examines the relationship between delinquent behavior and gang involvement in China. We assess the feasibility of self-report methodology in China and whether established findings in US and European settings on the relationship between gang involvement, violence specialization, and delinquent behavior extend to the Chinese context. Methods Data were gathered from 2,245 members of a school-based sample in Changzhi, a city of over 3 million people in Northern China. Drawing from a detailed survey questionnaire that measures prominent theoretical constructs, multi-level item response theory modeling was used to examine the association of gang involvement with general and specific forms of delinquency, notably violence specialization. Results Over half of the sample engaged in some form of delinquency over the prior year. Eleven percent of the sample reported gang involvement. Large bivariate differences in overall delinquency and violence specialization between gang and non-gang youth were observed. Multivariate analyses with measures of low self-control, household strains, family and school attachment, parental monitoring, and peer delinquency reduced the bivariate effect sizes, but current and former gang members had higher log odds of overall delinquency and violence specialization. Conclusion In helping fill gaps of knowledge on gangs and delinquency in the world’s most populous country, this study observed self-reported rates of delinquency and gang involvement not unlike Western countries. Findings on the relationship between gangs and delinquency, particularly violence, are consistent with the current literature and support the invariance hypothesis of gang involvement.